Effect of Denosumab or Alendronic Acid on the Progression of Aortic Stenosis: A Double-Blind Randomized Controlled Trial. Issue 25 (29th April 2021) - Pawade, Tania A.; Doris, Mhairi K.; Bing, Rong; White, Audrey C.; Forsyth, Laura; Evans, Emily; Graham, Catriona; Williams, Michelle C.; van Beek, Edwin J.R.; Fletcher, Alison; Adamson, Philip D.; Andrews, Jack P.M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Valvular calcification is central to the pathogenesis and progression of aortic stenosis, with preclinical and observational studies suggesting that bone turnover and osteoblastic differentiation of valvular interstitial cells are important contributory mechanisms. We aimed to establish whether inhibition of these pathways with denosumab or alendronic acid could reduce disease progression in aortic stenosis. Methods: In a single-center, parallel group, double-blind randomized controlled trial, patients >50 years of age with calcific aortic stenosis (peak aortic jet velocity >2.5 m/s) were randomized 2:1:2:1 to denosumab (60 mg every 6 months), placebo injection, alendronic acid (70 mg once weekly), or placebo capsule. Participants underwent serial assessments with Doppler echocardiography, computed tomography aortic valve calcium scoring, and 18 F-sodium fluoride positron emission tomography and computed tomography. The primary end point was the calculated 24-month change in aortic valve calcium score. Results: A total of 150 patients (mean age, 72±8 years; 21% women) with calcific aortic stenosis (peak aortic jet velocity, 3.36 m/s [2.93–3.82 m/s]; aortic valve calcium score, 1152 AU [655–2065 AU]) were randomized and received the allocated trial intervention: denosumab (n=49), alendronic acid (n=51), and placebo (injection n=25, capsule n=25; pooled for analysis). Serum C-terminal telopeptide, a measure of bone turnover, halved from baseline to 6 months with denosumab (0.23 [0.18–0.33 µg/L] to 0.11 µg/L [0.08–0.17 µg/L]) and alendronic acid (0.20 [0.14–0.28 µg/L] to 0.09 µg/L [0.08–0.13 µg/L]) but was unchanged with placebo (0.23 [0.17–0.30 µg/L] to 0.26 µg/L [0.16–0.31 µg/L]). There were no differences in 24-month change in aortic valve calcium score between denosumab and placebo (343 [198–804 AU] versus 354 AU [76–675 AU]; P=0.41) or alendronic acid and placebo (326 [138–813 AU] versus 354 AU [76–675 AU]; P =0.49). Similarly, there were no differences in change in peak aortic jet velocity or 18 F-sodium fluoride aortic valve uptake. Conclusions: Neither denosumab nor alendronic acid affected progression of aortic valve calcification in patients with calcific aortic stenosis. Alternative pathways and mechanisms need to be explored to identify disease-modifying therapies for the growing population of patients with this potentially fatal condition. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02132026.